2011
DOI: 10.1016/j.vaccine.2011.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an effect of BCG revaccination on incidence of tuberculosis in school-aged children in Brazil: Second report of the BCG-REVAC cluster-randomised trial

Abstract: BCG revaccination is still used in some tuberculosis endemic countries. Until now, the little evidence available suggested that BCG revaccination confers very limited additional protection, although there was no information on whether protection depends on the setting and age of revaccination, or if protection increases with time since vaccination. Here we report on an extended follow up of the BCG-REVAC trial, a cluster randomised trial conducted in the Brazilian cities Salvador and Manaus including over 200,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 11 publications
3
68
0
3
Order By: Relevance
“…However, a protein vaccine is much less efficient BCG-REVAC cluster-randomized trial in Brazil has confirmed that revaccination with BCG does not increase its protective efficacy against TB, particularly not in regions with high incidence of nontuberculous mycobacteria. 46 In experimental animal models, decreased survival of guinea pigs infected with Mycobacterium tuberculosis was reported after multiple BCG vaccinations. 47 Finally, in an experimental mouse model, a booster vaccination with BCG did not improve the protective efficacy against BU.…”
Section: Vaccination Methodsmentioning
confidence: 99%
“…However, a protein vaccine is much less efficient BCG-REVAC cluster-randomized trial in Brazil has confirmed that revaccination with BCG does not increase its protective efficacy against TB, particularly not in regions with high incidence of nontuberculous mycobacteria. 46 In experimental animal models, decreased survival of guinea pigs infected with Mycobacterium tuberculosis was reported after multiple BCG vaccinations. 47 Finally, in an experimental mouse model, a booster vaccination with BCG did not improve the protective efficacy against BU.…”
Section: Vaccination Methodsmentioning
confidence: 99%
“…With the extended 4 y of follow-up and the additional cases accrued, the previous study in Brazil revealed that the overall vaccine efficacy was 12% as compared with9% for the 5-year follow up, 97 indicating that the revaccination with BCG provided the additional protective efficacy against TB, and this efficacy varied with distance from equator, ranging from 1% of Manaus (with short distance from equator) to 19% of Salvador (with long distance from equator). 97 This difference further strengthened the earlier hypothesis that BCG vaccination offers higher efficacy in low NTM prevalence. Taken together, revaccination with BCG may have some available protective effectiveness in some certain settings.…”
Section: Revaccination Of Bcgmentioning
confidence: 97%
“…19 Barreto et al reported a duration of protection of 15-20 y in subjects vaccinated at birth (efficacy after 15-20 y 39%, 95% CI 9-58%), 25 and Weir et al a duration of immunological memory of at least 14 y in subjects vaccinated at birth or during adolescence. 31 The five BCG revaccination studies identified were 3 randomized clinical trials, [32][33][34] one cohort study, 35 and one casecontrol study, 36 none of which was carried out in Europe or North America. All of them showed that a second vaccination at the age of 19 months or during school age had no additional effect in comparison with a single administration, 32,33,35,36 although a follow-up study carried out 9 y after a clinical trial in Brazil has recently documented that, at higher latitudes, there may be some advantage in revaccinating children aged <11 y.…”
Section: How Long Does the Protection Provided By Bcg Vaccine Last Amentioning
confidence: 99%
“…All of them showed that a second vaccination at the age of 19 months or during school age had no additional effect in comparison with a single administration, 32,33,35,36 although a follow-up study carried out 9 y after a clinical trial in Brazil has recently documented that, at higher latitudes, there may be some advantage in revaccinating children aged <11 y. 34 …”
Section: How Long Does the Protection Provided By Bcg Vaccine Last Amentioning
confidence: 99%